2017
DOI: 10.18192/uojm.v7i1.1512
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Social Accountability in Medical School Education: a Tale of Five Students’ Integration into Vancouver’s Downtown Eastside

Abstract: P a g e 1 | U O J M e P u b | J a n u a r y 2 0 1 7Les professeurs de médecine reconnaissent que la responsabilité sociale est un pilier de l'éducation médicale canadienne; néan-moins, c'est un concept difficile à enseigner didactiquement. De plus en plus de preuves appuient l'intégration de la responsabilité sociale au curriculum médical à travers l'engagement communautaire. Heureusement, la Faculté de Médecine de l'Université de la Colombie-Britannique permet aux étudiants de participer à l'apprentissage par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A recent study conducted in Morocco showed similar results and reported that students who do social services perceived a better perception of SA (Sebbani et al, 2021). It is believed that engaging students in communitybased learning sites representing the actual population ensure the acquisition of well-defined competencies for more efficient health service delivery and encourage medical students to feel their school impact on the community and, thereby, improve their perceived SA (Boelen, 2016;Clithero et al, 2017;Roughead et al, 2017;Woolley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in Morocco showed similar results and reported that students who do social services perceived a better perception of SA (Sebbani et al, 2021). It is believed that engaging students in communitybased learning sites representing the actual population ensure the acquisition of well-defined competencies for more efficient health service delivery and encourage medical students to feel their school impact on the community and, thereby, improve their perceived SA (Boelen, 2016;Clithero et al, 2017;Roughead et al, 2017;Woolley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent case study by the University of British Columbia (UBC), medical students investigated the impact of a community-based learning opportunity on their sense of appreciation around the importance of social accountability and health advocacy [13]. The opportunity provided second-year medical students the ability to take part in a community-service option as an alternative to classroom-based learning, providing medical students the opportunity to work directly with vulnerable and marginalized segments of the population.…”
Section: Community Engagement Is Keymentioning
confidence: 99%
“…Others point out that medical education offers limited opportunities to work with socially disadvantaged and marginalized segments of the population, which is required to instrument the knowledge and skills necessary to be an effective health advocate [1,6,9,11,12]. Medical programs that do provide experiential and community service learning initiatives with a focus on health advocacy and the social determinants of health reported that these types of authentic learning activities are key to enabling students to gain a greater insight into how health advocacy can be applied [13,14]. Students are enabled to develop a greater appreciation of the root causes and subsequent effects of health disparities, and a greater sensitivity to the circumstances of people in society who are rendered vulnerable because of various socioeconomic factors that prevent them from protecting and preserving their well-being [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…These approaches have seen success at the few medical schools beginning to implement these ideas into practice. Medical schools have reported these experiences as key to their students deeper understanding of the social intricacies in health disparities ( Roughead et al, 2017 ). Students are given a greater sensitivity to communities they engage with and learn about the specific circumstances making these populations so vulnerable ( Ventres & Dharamsi, 2015 ; Ventres et al, 2018 ).…”
Section: The Role Of Community-engaged Learningmentioning
confidence: 99%